PO.7.145 Active skin involvement in patients with systemic lupus erythematosus: analysis of the impact on health-related quality of life and patient perception of health status. (27th September 2022) - Elefante, E; Signorini, V; Stagnaro, C; Zucchi, D; Trentin, F; Salvi, I; Lazzareschi, C; Carli, L; Ferro, F; Tani, C; Mosca, M
Abstract : Purpose skin involvement can severely alter body image thus representing a major concern for patients with Systemic Lupus Erythematosus (SLE). The aim of this study was to analyze the impact of active skin involvement on Health-Related Quality of Life (HRQoL), mood disorders and self-perception of disease activity in a monocentric cohort of SLE patients. Methods: a cross-sectional study including consecutive outpatients with SLE with active skin involvement. The severity of skin lesions was assessed through the CLASI index. Consecutive SLE outpatients with at least one active disease manifestation, but without active skin involvement or irreversible skin damage served as a control group. The following data have been collected: demographics, clinical and laboratory data, SLEDAI-2K and SLICC-DI. Each patient completed the following Patient-Reported Outcomes (PROs): SF-36, FACIT-F, LIT for disease burden, SLAQ for self-assessment of disease activity; the HADS for anxiety and depression was available for a subgroup of patients. Patients with skin involvement also completed the SKINDEX-16 (a questionnaire for the evaluation of HRQoL in patients with dermatological conditions). Results we enrolled 72 consecutive SLE patients, 38 with active skin lesions ('skin group') and 34 without active mucocutaneous manifestations or irreversible skin damage ('no-skin group'); 88.9% were female, 94.4% Caucasians. Mean age at enrollment was 43.9 ± 12.2 years and median disease duration was 11.5 (IQR 7–18.5) years. In the 'skin group' the median CLASI activity score was 5 (IQR 3–7.5) and the median CLASI damage score was 1 (IQR 0–4). In the 'no-skin group', we found a significantly higher percentage of patients with active hematological and renal manifestations (p<0.01). No other significant differences emerged between the two groups with respect to age, disease duration, disease activity and damage, ongoing treatment and fibromyalgia. By comparing PROs results between the two groups, we found no significant differences for the SF-36, the LIT and the FACIT-F. However, although the SLEDAI score did not significantly differ between the two groups, we found that patients in the 'skin group' had a significantly higher score of the SLAQ questionnaire compared to patients in the 'no-skin group' (p<0.01). The HADS questionnaire was available for 50 patients: patients with active skin involvement presented significantly higher scores for depressive symptoms compared to patients without skin manifestations (p=0.01). Finally, among patients with active skin lesions, we did not demonstrate a significant correlation between the CLASI activity score and the scores of all PROs used, not even with the SKINDEX, which is specific for dermatological conditions. Conclusion although skin involvement is not generally considered a severe disease manifestation in SLE, it seems to be strongly associated with patients' perception of higher disease activity and with depressive symptoms. These results underline as skin involvement still represents an unmet need in the management of patients with SLE, with a potentially negative impact on patient satisfaction with the care process.